The Korean War: "The Forgotten War" - Stein, R. Conrad (Berkeley Heights, NJ Enslow Publishers, Inc., 1994)
Many Americans in 1950 could hardly believe that the United States was being called to war in the faraway nation of Korea.
Keywords: Korean War, 1950-1953.